2014
DOI: 10.1186/s40467-014-0018-0
|View full text |Cite
|
Sign up to set email alerts
|

Similarity in fuzzy systems

Abstract: This paper proposes to study the concept of similarity and its use in the design of fuzzy system. The concept of similarity relation is effectively used in fuzzification of crisp values. Similarity index is used in measuring approximate (graded) equality of fuzzy sets over a given universe of discourse. It is proposed to use such an index in modifying a fuzzy relation. Different similarity measures in the literature are elucidated, and a comparative study between different pairs of fuzzy sets is presented. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…A fuzzy measure based on matching functions [17] is also included in Table I as it uses the maximum t-conorm. A detailed discussion of set-theoretic similarity measures for fuzzy sets can be found in [20] and [21].…”
Section: Fuzzy Set-theoretic Similarity Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…A fuzzy measure based on matching functions [17] is also included in Table I as it uses the maximum t-conorm. A detailed discussion of set-theoretic similarity measures for fuzzy sets can be found in [20] and [21].…”
Section: Fuzzy Set-theoretic Similarity Measuresmentioning
confidence: 99%
“…We note that Eq. (7)behaves like a fuzzy measure mentioned in[21] for the minimum t-norm, though the origin of this measure is unknown.…”
mentioning
confidence: 99%
“…This motivates the introduction of similarity based reasoning techniques as proposed in [12] [13] [14]. A brief review work on similarity based approximate reasoning, in general, can be found in [10] [15]. A detailed description of similarity related reasoning can also be found in [12].…”
Section: Similarity Based Fuzzy System (Sbfs)mentioning
confidence: 99%
“…We interpret the result as a conditional fuzzy relation. Then, the similarity value is used to modify the conditional relation [10]. Such a modification of relation may also be performed in many ways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation